-x-(-2x-3)²=-4x²-3(x-2)
Răspunsuri la întrebare
Răspuns de
0
inmultim cu (-1)
x+(-2x-3)²=4x²+3(x-2)
tinem cont ca (-a-b)²= [(-1) (a+b)]²= (-1)²(a+b)²=1*(a+b)²= (a+b)²
x+(2x+3)²=4x²+3x-6
x+4x²+12x+9=4x²+3x-6
13x+9=3x-6
13x-3x=-6-9
10x=-15
2x=-3
x=-3/2
care verifica ecuatia
x+(-2x-3)²=4x²+3(x-2)
tinem cont ca (-a-b)²= [(-1) (a+b)]²= (-1)²(a+b)²=1*(a+b)²= (a+b)²
x+(2x+3)²=4x²+3x-6
x+4x²+12x+9=4x²+3x-6
13x+9=3x-6
13x-3x=-6-9
10x=-15
2x=-3
x=-3/2
care verifica ecuatia
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Geografie,
9 ani în urmă